MASP: Proposal for Application in a Telecommunications Service Provider to Increase Quality in the Maintenance Sector - Gomes, Luis Felipe Fortunato; Longhini, Tatielle Menolli (Brazilian Journal of Production Engineering, 2025)
This work was developed in a company that provides telecommunication services focused on internet distribution, focusing on fiber optic broadband. The study was specifically aimed at the company's maintenance sector, which has a high rate of visits, as well as low quality and lack of standardization in the sector's procedures, leading to several customer complaints and cancellations. Therefore, the present work has the objective of applying the MASP / PDCA to identify and analyze the problems encountered in the maintenance calls. Thus, data were collected from the Work Orders of the period studied, in order to make it possible to recommend the Pareto Diagram, Ishikawa Diagram, 5 Whys and 5W2H tools to be applied, to prioritize the causes, to verify the root of the problem and to elaborate the proposed solution. The application of the tools made possible the analysis of the process as a whole, allowing the identification of the problems and, finally, the elaboration of the improvement proposals. Consequently achieving the initial goal of proposing quality improvements to the maintenance industry.
Keywords: MASP; PDCA; Quality; Maintenance; Telecommunication